PERSEPSI MASYARAKAT TERHADAP USAHA TANI TANAMAN KARET (Hevea brasiliensis) DI DESA NANGA TEKUNGAI KECAMATAN SERAWAI KABUPATEN SINTANG - Satria, Yulius Yudhi; Surachman, Maman; wati, Pur (JURNAL HUTAN LESTARI, 2013)
Rubber farm has been in interest by society in the village of Nanga Tekungai Serawai District district 1990'an Sintang of years as a sideline livelihood. Although rubber farming community is a side job, but the income of the people in the village of Nanga Tekungai of farm produce sizeable rubber. This study aims to determine the public perception of farming as well as the rubber plant wants to know whether there is any influence of knowledge, cosmopolitan and income to the farming community that the love of rubber horticultural society in the village of Nanga Tekungai. This study uses a descriptive survey and associative with interview techniques and tools such as questionnaires form lists a number of questions posed to the respondent. Public perception of rubber farming is likely to be positive, with 71 respondents (69.61%) of the total 102 respondents, it demonstrates that people agree and do not hesitate in getting rubber farming. Conclusion The results showed that people in the village of Nanga Tekungai District Serawai Sintang likely to have positive perceptions of rubber farming and knowledge factors, income and cosmopolitan influence public perception in the village of Nanga Tekungai District Serawai Sintang the rubber farm. Keywords : public perception, rubber farm, Nanga Tekungai.